Safety and Efficacy of Intravenous Zanamivir in Preventing Experimental Human Influenza A Virus Infection - Calfee, David P. (American Society for Microbiology, 1999)
Zanamivir is a potent inhibitor of influenza A and B virus neuraminidases and is active topically in experimental and natural human influenza. We conducted this double-blinded, placebo-controlled study to evaluate the safety and efficacy of intravenously administered zanamivir. Susceptible volunteers were randomized to receive either saline or zanamivir (600 mg) intravenously twice daily for 5 days beginning 4 h prior to intranasal inoculation with ∼10(5) 50% tissue culture infectious doses (TCID(50)) of influenza A/Texas/36/91 (H1N1) virus. Reductions in the frequency of viral shedding (0% versus 100% in placebo, P < 0.005) and seroconversion (14% versus 100% in placebo, P < 0.005) and decreases in viral titer areas under the curve (0 versus 11.6 [median] log(10) TCID(50) · day/ml in placebo, P < 0.005) were observed in the zanamivir group, as were reductions in fever (14% versus 88% in placebo, P < 0.05), upper respiratory tract illness (0% versus 100% in placebo, P < 0.005), total symptom scores (1 versus 44 [median] in placebo, P < 0.005), and nasal-discharge weight (3.9 g versus 17.5 g [median] in placebo, P < 0.005). Zanamivir was detectable in nasal lavage samples collected on days 2 and 4 (unadjusted median concentrations, 10.5 and 12.0 ng/ml of nasal wash, respectively). This study demonstrates that intravenously administered zanamivir is distributed to the respiratory mucosa and is protective against infection and illness following experimental human influenza A virus inoculation.